Descriptive comparison of SME performance between Iran and UK - Sorooshian, Shahryar; Zulkifli, Norzima; Ismail, Mohd Yusof (IDOSI Publications, 2011)
This paper is a part of an on-going research effort to derive, characterise and employ an empirically-based development taxonomy for Small and Medium Enterprises (SMEs) aim to help the government SMEs strategists within which the companies operating to benchmark and to determine the level of their success potential and relate it to the benefit to the region. This research attempt to examines the general characteristics and performance capabilities of Chief Executive Officer (CEO) of Iranian SMEs compared with SME CEOs of United Kingdom (UK) using data made through independent SME studies in Iran and UK. Data from 321 SME CEO in Iran and 132 SME CEO in UK analysed. Descriptive statistics for various enterprise performance potential and CEO's characteristics facilitate provide a comparison analysis between Iranian SMEs and UK's. Main result of this study is a deep understanding of SME capacities in Iran and UK.